The deceivers - McDowell, Josh.; Hostetler, Bob, 1958-; Bellis, David H. (Wheaton, Ill. : Tyndale House, 2003)
Three high school students on a wilderness trip with their church group struggle with moral decisions, while several of Satan's underlings try to lead them astray. Includes sections that relate the story to real-life decisions and matters of spiritual growth.
"A NovelPlus"--Cover.
Keywords: Christian life -- Fiction; Conduct of life -- Fiction; Wilderness survival -- Fiction; Christian life -- Juvenile fiction; Conduct of life -- Juvenile fiction; Wilderness survival -- Juvenile fiction